Polish Media about Act 2.0(The Constitution for Science) - Mrozowska, Sylwia; Ryłko-Kurpiewska, Anna (Communication Today, 2020)
The article ﬁts in with research on discursive determinants of the condition of the university and focuses on the analysis of media messages about the main assumptions of Act 2.0 (the Constitution for Science). It is considered an important stage of systemic changes in Polish science and higher education system thirty years after the beginning of the political transformation and ﬁfteen years after accession to the European Union. The ﬁrst part of the article deals with presenting the conditions of the modernisation of the higher education system in the context of external and internal factors of the transformation. The second part discusses the speciﬁcity of media messages characterising the Polish act. The way of reporting about changes resulting from the act outlined by the media is to be one of the determinants of social perception of positive changes occurring in the area of higher education. This is demonstrated by the subject matter, the genre of the statements, contextual conditions: time, place, the current socio-political situation, vocabulary and collocations.